Providing Periodic Press Information For The Social And Household Population Regarding Housing - Yoldasheva Zubayda Hamidovna (Genius Journals, 2024)
Today, in the rapidly changing information age (21st century), the scope of mass media activities and influence on human and social life is increasing at an unprecedented level. Especially at a time when the Republic of Uzbekistan is an independent country and facing the world, the press has been making a significant contribution to covering current issues. Surkhan oasis press also has a long history
Keywords: Surkhan tongi; Sariosia; social and household life; mass media